Novelties in Costa Rican aroids (Araceae) with nomenclatural notes - Ortiz, Orlando O. (2020)
Background and Aims: Araceae is a worldwide family of herbaceous plants, most notable for its striking morphological diversity and broad habitat di-versity. It comprises eight subfamilies, 143 genera, and 3667 species. The Central American region has about 780 species, of which 262 are distributedin Costa Rica. In this contribution, we include four new aroid records for the Costa Rican flora belonging to the genera Anthurium, Philodendron, and Spathiphyllum. In addition, nomenclatural aspects of A. myosuroides are discussed.Methods: The new records resulted from fieldwork on Fila Anguciana, Cerro Turrubares, and Volcán Miravalles. The correct taxonomic identity of the species was confirmed based on literature and comparison with herbarium specimens, especially type specimens from the herbaria of the Univer-sidad de Panama (PMA) and the Missouri Botanical Garden (MO), as well as consultation of the JSTOR Global Plants database and the collections of the Muséum National d'Histoire Naturelle de Paris (P) online. Descriptions, taxonomic discussions, and figures of the morphological characteristics of the new records are provided.Key results: We present Anthurium roseospadix, A. myosuroides, Philodendron pseudauriculatum and Spathiphyllum dressleri as new records for the Costa Rican flora. Moreover, lectotypification for Pothos myosuroides is proposed.Conclusions: Considering the new records presented in this work, the aroid flora of Costa Rica now comprises 266 species, and the total species numbers for Anthurium, Philodendron, and Spathiphyllum increased to 94, 63, and 10, respectively.Key words:Anthurium, Cerro Turrubares, Fila Anguciana, Flora of Costa Rica, Philodendron, Spathiphyllum, Volcán Miravalles.